Penguatan kelembagaan menuju destinasi utama pendidikan Islam global : menyongsong World Class University - Penguatan_kelembagaan_menuju_destinasi_utama_ pendidikan_Islam_global_:_menyongsong_World_Class_Univ (UIN Maliki Press, 2014)
st,3./ws.c.1-6